Preventive effects of quercetin against foot-and-mouth disease virus in vitro and in vivo by inducing type I interferon - Lee, Gyeongmin; Kang, Hyo Rin; Kim, Aro; Park, Jong-Hyeon; Lee, Min Ja; Kim, Su-Mi (Frontiers in Microbiology, 2023)
Foot-and-mouth disease (FMD) is an acute contagious infectious disease that affects cloven-hoofed animals. Although current emergency FMD vaccines only take effect seven days after vaccination, antiviral agents, such as quercetin, which is a common flavonoid, could reduce the spread of FMD virus (FMDV) during outbreaks. We investigated the in vitro and in vivo antiviral effects of quercetin against FMDV. Analysis of viral copy numbers showed that quercetin had a dose-dependent inhibitory effect on FMDV at concentrations between 19.5 and 1250 µM in porcine cells. In addition, we observed a quercetin-induced interferon (IFN)-α protein and interferon-stimulated gene (ISG) upregulation in swine cells. Enzyme-linked immunosorbent assay of sera revealed that quercetin induces the production of IFN-α, IFN-β, IFN-γ, interleukin (IL)-12, and IL-15 in mice. Inoculation of mice with quercetin or a combination of quercetin with an inactivated FMD vaccine enhanced both the survival rate and neutralizing antibody titer. Therefore, we suggest the use of quercetin as a novel and effective antiviral agent for controlling FMDV infection; however, further investigation of its application in livestock is required.